2023
DOI: 10.1093/femsec/fiad072
|View full text |Cite
|
Sign up to set email alerts
|

Proportions of taxa belonging to the gut core microbiome change throughout the life cycle and season of the bark beetleIps typographus

Abstract: The European spruce bark beetle, Ips typographus, is a serious pest of spruce forests in Europe, and its invasion and development inside spruce tissues are facilitated by microorganisms. We investigated the core gut bacterial and fungal microbiomes of I. typographus throughout its life cycle in spring and summer generations. We used cultivation techniques and molecular identification in combination with DNA and RNA metabarcoding. Our results revealed that communities differ in the throughout the life cycle and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 87 publications
3
10
0
1
Order By: Relevance
“…There has been growing interest in understanding the role of insect-microbial association in shaping the plasticity of insects in recent times. For instance, a recent study on Eurasian spruce bark beetles, I. typographus, reported the developmental stage and the geo-location as drivers in shaping the beetle-microbial association (27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There has been growing interest in understanding the role of insect-microbial association in shaping the plasticity of insects in recent times. For instance, a recent study on Eurasian spruce bark beetles, I. typographus, reported the developmental stage and the geo-location as drivers in shaping the beetle-microbial association (27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, our understanding of bark beetles as holobionts is restricted. Few studies have evaluated microbial acquisition and succession in bark beetles (26)(27)(28)(29). In addition, limited studies in pine bark beetles have focused on understanding the effect of environment and metamorphosis that can cause comprehensive changes in the beetle microbiome, resulting in distinct bacterial communities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While previous studies were based on pooled I. typographus guts from one restricted geographic area (Chakraborty et al 2020; Fang et al 2020; Yu et al 2022; Veselská et al 2023), our approach allowed a fine-scale analysis of several European populations on a single individual level. Our analysis revealed that the genera Erwinia and Pseudoxanthomonas which were previously described in I. typographus in the Czech Republic and in China (Chakraborty et al 2020; Fang et al 2020; Yu et al 2022) can be considered the core bacterial community being present in all individuals ( Erwinia ) and in 98.44% of the individuals ( Pseudoxanthomonas ).…”
Section: Discussionmentioning
confidence: 99%
“…Although our understanding of the bacterial community structure of I. typographus has increased in recent years (Chakraborty et al 2020; 2023; Fang et al 2020; Yu et al 2022; Veselská et al 2023), surprisingly little knowledge exists about the taxonomic composition and diversity across different geographic regions, epidemiological and overwintering phases. Here, we first describe the taxonomic composition and core-microbiome of I. typographus by characterizing the bacterial communities of different populations from a large area of Europe, including the four major refugial areas, in the Apennines, the Dinaric Alps on the Balkan Peninsula, the Carpathian Mountains and in the Russian plain (Tollefsrud et al 2009).…”
Section: Introductionmentioning
confidence: 99%